The abstracted real : speculations on experimental animated documentary - Hattler, Max (2022)
This paper proposes a debate around the documentary character of experimental animation by looking at examples of my personal animation practice which probe the use of real-world source materials in the construction of audio-visual experiences across abstract and concrete. By employing the aesthetics of abstraction in particular ways, these ‘abstracted’ animation works underline ambivalence and ambiguity in creating open-ended narratives which aim to question, undermine, or transcend their everyday sources. Through a discussion of theoretical positions around notions of realism, materiality, embodiment, indexicality, actuality and process, what becomes apparent is an intrinsic relation between ‘reality’ and ‘animation,’ whereby the viewer actively participates in meaning-making processes in the reception of the work. The claim of the paper is to identify abstracted animation in its capacity to create ‘thinking spaces’ which instead of representing reality, establish what can be called the Abstracted Real. Keywords: experimental animated documentary, abstracted animation, real-world abstractions, animation as a thinking space, indexicality, meaning making, the abstracted real.